Analisis Pendapatan Usaha Pada Peternakan Ayam Ras Petelur “SBK” (Simpang Bukit Kaba) Farm Desa Karang Jaya Kecamatan Selupu Rejang - Oktarizal, Ilham; Niarti, Upi (Politeknik Raflesia Press, 2024)
This research aims to analyze and find out the total production costs of Mr. Andianto's egg-laying chicken farm in 1 period 2023, the total sales of eggs from Mr. Andianto's farm in 1 period 2023, and the total profit/profit from Mr. Andianto's SBK FARM egg-laying chicken farming business. in 1 Period 2023. The method used in this research is a quantitative descriptive method. The results of the analysis that I got after many calculations show that the total production costs of Mr. Andianto's egg laying chicken farming business for 1 period 2023 is IDR 543,468,000, the total income from selling Mr. Andianto's eggs for 1 period 2023 is IDR 777,600,000, and the total profit of Mr Andianto's egg-laying chicken farm for the period 2023 is IDR 234,132,000. And shows that this business is profitable and very promising now and in the future, because the demand for eggs will never stop, so this business is worth running.